Analysis of planar compliant mechanisms based on non-linear analytical modeling including shear and lateral contraction. (October 2021) - Henning, Stefan; Zentner, Lena
Highlights: Bending, shear and lateral contraction are considered for large deflections. A GUI for the analysis and synthesis of compliant mechanisms is presented. Example mechanisms with concentrated and distributed compliance are considered. The analytical model is validated by FEM simulations and measurements. The user interface allows fast and accurate analysis of planar compliant mechanisms. Abstract: Compliant mechanisms are commonly used in precision engineering while analyzing their deflection is particularly challenging. Often, FEM simulations are chosen in an iterative process. Analytical approaches that consider pure bending, shear or other effects are usually limited to the mechanism as a system. However, certain configurations comprise compliant elements with different aspect ratios. The aim of this paper is to integrate the theories of shear and lateral contraction into a unified form with the existing theory of bending for large deflections and make them applicable individually for specific sections of continuous compliant mechanisms. Recommendations are made as to when which theory should be used. Building on that, a comprehensive tool for analyzing compliant mechanisms developed in Python is introduced. The tool offers the possibility to create arbitrary compliant mechanisms including branched links and various boundary conditions. A tool for parametric studies allows to optimize the given geometry for realizing a specific motion task. Further, FEM and measurement results correlate well with the application results. The presented user interface can be beneficial for the accelerated analysis and synthesis of compliant mechanisms.